A novel strategy of co-expressing CXCR5 and IL-7 enhances CAR-T cell effectiveness in osteosarcoma - Hui, Xinhui; Farooq, Muhammad Asad; Chen, Yiran; Ajmal, Iqra; Ren, Yaojun; Xue, Min; Ji, Yuzhou; Du, Bingtan; Wu, Shijia; Jiang, Wenzheng (Frontiers in Immunology, 2024)
Solid tumors are characterized by a low blood supply, complex stromal architecture, and immunosuppressive milieu, which inhibit CAR-T cell entry and survival. CXCR5 has previously been employed to increase CAR-T cell infiltration into CXCL13+ cancers. On the other hand, IL-7 improves the survival and persistence of T cells inside a solid tumor milieu. We constructed a novel NKG2Dbased CAR (C5/IL7-CAR) that co-expressed CXCR5 and IL-7. The human osteosarcoma cell lines U-2 OS, 143B, and Mg63 highly expressed MICA/B and CXCL13, thus presenting a perfect avenue for the present study. Novel CAR-T cells are superior in their activation, degranulation, and cytokine release competence, hence lysing more target cells than conventional CAR. Furthermore, CXCR5 and IL-7 co-expression decreased the expression of PD-1, TIM-3, and TIGIT and increased Bcl-2 expression. Novel CAR-T cells show enhanced proliferation and differentiation towards the stem cell memory T cell phenotype. C5/IL7-CAR-T cells outperformed conventional CAR-T in eradicating osteosarcoma in mouse models and displayed better survival. Additionally, CXCR5 and IL-7 coexpression enhanced CAR-T cell numbers, cytokine release, and survival in implanted tumor tissues compared to conventional CAR-T cells. Mechanistically, C5/IL7-CAR-T cells displayed enhanced STAT5 signaling. These findings highlight the potential of CXCR5 and IL-7 co-expression to improve CAR-T cell therapy efficacy against osteosarcoma.